Evidence-based practice in road casualty reduction. Issue 5 (4th October 2007) - Hewson, Paul
Abstract : An alternative way is analyzed in which practitioners working to reduce road injury can assess research evidence. Familiarization with published research makes practitioners more confident about evaluating practice in a formal manner.